Peculiarities of Heavy, Oversized and Hazardous Cargo Trasportation - Khachatryan, S. N. (ՀԱԱՀ հիմնադրամ)
The article analyzes the peculiarities of different transport modes indicating the advantages of cargo transportation by motor vehicles. It is shown that the transportation of both dangerous and oversized heavy cargo, especially in mountainous areas, requires strict observance of safety rules, especially when about 20 % of the total cargo transportation includes hazardous cargo. It was also noted that there are tools and equipment (cargos) that requires professional rolling stock for transportation, while for some cases special means should be created for transporting the given cargo, including platform, trailer, trolley, etc.
Keywords: Agricultural Engineering